2007
DOI: 10.1093/intimm/dxm097
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin  1 activates the TLR9/MyD88/IRF7-dependent murine cytomegalovirus sensing for induction of anti-viral responses in vivo

Abstract: Reactivation of latent human cytomegalovirus following allogeneic transplantation is a major cause of morbidity and mortality and predisposes to severe complications. Thymosin alpha1 (Talpha1), a naturally occurring thymic peptide, is approved for treatment of some viral infections and as an immune adjuvant. Talpha1 successfully primed dendritic cells (DCs) for anti-microbial T helper type 1 resistance through Toll-like receptor (TLR) 9 signaling. We sought to determine here whether Talpha1 could play a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…There have been a number of other immunomodulatory activities attributed to extracellular ProTα or peptides derived from it, including up-regulation of HLA-DR, IL-2 receptor, dendritic cell maturation, chemotaxis, anti-viral, anti-cancer, and anti-fungal activities (19)(20)(21). In fact, the Tα1 peptide, which did not display anti-HIV-1 activity, has been associated with direct stimulation of TLR9, activation of the MyD88 pathway, and production of IL-10 in dendritic cells in which Tα1 peptide has immunomodulatory activity and stimulates an anti-fungal response in a murine model of candida (20).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of other immunomodulatory activities attributed to extracellular ProTα or peptides derived from it, including up-regulation of HLA-DR, IL-2 receptor, dendritic cell maturation, chemotaxis, anti-viral, anti-cancer, and anti-fungal activities (19)(20)(21). In fact, the Tα1 peptide, which did not display anti-HIV-1 activity, has been associated with direct stimulation of TLR9, activation of the MyD88 pathway, and production of IL-10 in dendritic cells in which Tα1 peptide has immunomodulatory activity and stimulates an anti-fungal response in a murine model of candida (20).…”
Section: Discussionmentioning
confidence: 99%
“…10,28,29 TLR9 is critically required in the process of cytomegalovirus (CMV) sensing to assure rapid anti-viral responses. 30,31 The TLR9 ligand CpG prevents graft acceptance both by interfering with natural regulatory T-cell (Treg) function and by promoting the differentiation of Th1 effector T cells in vivo. 8,32 It is known that suppression of Tregs is associated with the development of BOS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent insights into the molecular mechanisms of Ta1's pleiotropy have revealed its central role in modulating DC function, which is consistent with the ability of Ta1 to induce different forms of immunity and tolerance [10]. Results have shown that Ta1: i) primed DCs for antifungal T-helper (Th)1 resistance through Tolllike receptor (TLR)/MyD88-dependent signaling and this translated in vivo to protection against fungal infections [6]; ii) activated plasmacytoid DCs via the TLR9/MyD88-dependent viral recognition, thus leading to the activation of IFN regulatory factor 7 and the promotion of the IFN-a/ IFN-g-dependent effector pathway, and this resulted in protection against primary murine cytomegalovirus infection [11]; and iii) induced indoleamine 2,3-dioxygenase (IDO)1 activity in DCs, thus affecting tolerization toward self as well as microbial non-self antigens, and this resulted in vivo in transplantation tolerance [8] and protection from inflammation and allergy [12]. Evidence suggests that the ability of Ta1 to signal through disparate TLRs on DC subsets may occur through the interaction with multiple, yet distinct, TLR ligands, either endogenous or exogenous [10].…”
Section: From Pleiotropy To Molecular Mechanisms Of a System-orientedmentioning
confidence: 99%